Effect of organic and inorganic sources of nitrogen on productivity and soil fertility under rice (Oryza sativa) -wheat (Triticum aestivum) crop sequence - PAIKARAY, R K; MAHAPATRA, B S; SHARMA, G L (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was carried out during 1996-97 to 1997-98 to evaluate the effectiveness of prickly sesban [Sesbania cannabina (Retz.) Pers.] (green-manure), wheat (Triticum aestivum L. emend. Fiori & Paol.)-straw incorporation and inclusion of summer cowpea [(Vigna unguiculata (L.) Walp.] fodder in rotation along with nitrogen in rice (Oryza sativa L.)-wheat system. Grain yield of rice with Sesbania green-manure with 40 kg N/ha (5.73 tonnes/ha), inclusion of cowpea fodder with 80 kg N/ha (5.70 tonnes/ha) and wheat straw incorporation with 80 kg N/ha to rice crop (5.79 tonnes/ha) were statistically similar with no organic N with 120 kg N/ha (5.71 tonnes/ha), indicating saving of 80 kg N/ha for green-manuring and 40 kg N/ha each for cowpea fodder and wheat straw incorporation. Sesbania green-manuring to rice increased the wheat grain yield by about 0.4 tonne/ha. The highest grain yield of wheat (4.48 tonnes/ha) was recorded from Sesbania green-manuring to rice with 120 kg N/ha to both of rice and wheat crop in the cropping system. Soil fertility in terms of organic carbon (0.03-0.06%), available N (5.8-22.0 kg/ha), P (1.4-3.8 kg/ha) andK (2.2-17.9 kg/ha) increased under green-manure, wheat-straw incorporation, summer cowpea. fodder and at higher levels of inorganic N. Only available K had negative balance in soils of cowpea fodder and the control plots and at lower levels of nitrogen.